2017
DOI: 10.1063/1.5012780
|View full text |Cite
|
Sign up to set email alerts
|

High performance field emission of silicon carbide nanowires and their applications in flexible field emission displays

Abstract: In this paper, a facile method to fabricate the flexible field emission devices (FEDs) based on SiC nanostructure emitters by a thermal evaporation method has been demonstrated. The composition characteristics of SiC nanowires was characterized by X-ray diffraction (XRD), selected area electron diffraction (SAED) and energy dispersive X-ray spectrometer (EDX), while the morphology was revealed by field emission scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Generally, LIGNs possess prominent, vertically aligned sharp-edged graphene materials (cf. Figure 2a), resulting in a high aspect ratio [17,18,26,27,28,29,30,31,32,33,34,35,36,37] and therefore excellent FEE performance. The J e versus time curve, measured at an applied field of 0.75 V/μm (Figure 4b), showed that the FEE current density was very stable for a period of 160 min.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, LIGNs possess prominent, vertically aligned sharp-edged graphene materials (cf. Figure 2a), resulting in a high aspect ratio [17,18,26,27,28,29,30,31,32,33,34,35,36,37] and therefore excellent FEE performance. The J e versus time curve, measured at an applied field of 0.75 V/μm (Figure 4b), showed that the FEE current density was very stable for a period of 160 min.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon carbide (SiC) nanowires have attracted considerable research interests for their wide band gap, unique electrical properties, and physical/chemical stability. These properties of SiC nanowires make them well-suited for constructing electronic devices for applications in harsh conditions of high power, high temperature, and high frequency. , The SiC nanowires can be commonly synthesized from a typical VLS process by the pyrolysis of polysilazane precursor on the carbon fabric substrates, where the Co alloy nanodroplets are utilized as the catalysts . Additionally, the SiC nanowires can also be obtained by direct reaction of carbon nanotubes with Si and I 2 or volatile SiO 2 .…”
Section: Synthesis Of Semiconductor Nanowires and Heterostructuresmentioning
confidence: 99%
“…Silicon carbide (SiC) has been widely applied in field emitters, [ 1–3 ] photodetectors, [ 4–6 ] and photoelectrochemical water splitting [ 7–11 ] because of its wide bandgap, high thermal conductivity, and excellent chemical inertness. [ 12 ] Recently, SiC has also been shown as an ideal material for high‐performance power electronic devices, [ 13 ] such as fin field‐effect transistor effect based metal‐oxide‐semiconductor field‐effect transistor [ 14,15 ] and insulated gate bipolar transistors (IGBTs), [ 16,17 ] which are used in high‐speed railways [ 18,19 ] and electric vehicles.…”
Section: Introductionmentioning
confidence: 99%